Impact of meteorological parameters in fruit splitting of Daisy mandarin under subtropical conditions - Kaur, Komalpreet; Gupta, Monika; Rattanpal, H. S.; Anand, Shubham; Singh, Gurteg; Raina, Dimpy (Frontiers in Plant Science, 2025)
Fruit splitting is a critical physiological disorder adversely affecting the fruit quality and marketability of citrus fruits, with its incidence closely associated with prevailing meteorological conditions. This study investigates the influence of weather parameters on fruit splitting in Daisy Mandarin. For this study, daily meteorological data on temperature, relative humidity and rainfall were obtained from the Agrometeorological Observatory, Punjab Agricultural University (PAU), Ludhiana. The results of this study revealed that a significantly higher incidence of fruit splitting was recorded in 2022 as compared to 2021, with key weather parameters playing a major role. Correlation and regression analyses identified that the maximum and minimum temperatures, morning and evening relative humidity and rainfall as the most influential factors. Higher temperatures accelerated the fruit growth, causing structural stress and subsequent splitting, while high humidity increased peel moisture content, making fruits more susceptible. Additionally, heavy rainfall following dry periods further intensified splitting due to rapid water uptake and internal pressure changes. These findings highlight the complex interactions between the meteorological parameters and underscore the need for adaptive management strategies to reduce fruit splitting under variable weather conditions.